CREATIVE APPROACHES TO STRENGTHENING THE COMPETITIVENESS OF THE ENTERPRISE - KRAVCHIK, Yuriy; RUZHITSKYI, Yuriy (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article emphasizes the importance of implementing creative approaches to strengthening the company’s competitiveness as the formation of a new style of strategic management of the processes of forming unique competitive advantages, improving the competitive situation, and increasing the competitive potential. The analysis of the latest research and publications proved the formation of various scientific assumptions regarding the selection and implementation of creative approaches to strengthening the competitiveness of the enterprise. Basic provisions for the implementation of creative approaches to strengthening the competitiveness of the enterprise have been determined. It was emphasized that a correctly chosen creative approach forms the rules and methods of effectively achieving the strategic goals of strengthening the company’s competitiveness. The basic procedures for the development and implementation of creative approaches to strengthening the competitiveness of the enterprise, which are focused on improving the resource management system and choosing strategic vectors for the development of entrepreneurial activity, have been defined. It was established that the use of creative approaches is a leading tool for effective management of the enterprise’s competitiveness, as a result of which it is possible to achieve its strengthening in a strategic perspective. Creativity is evidenced by the use of a completely new toolkit in strengthening the competitiveness of the enterprise and, importantly, in all areas of business development. Therefore, a creative approach should be considered as a strategic decision, the content of which involves the definition of goals and objectives, the achievement of which becomes possible if a completely new methodology is followed, and this is the conceptual basis of strengthening the competitiveness of the enterprise.